Loudun. The Body as a Field of War - Lancioni, Tarcisio (E|C, 2024)
The article proposes a semiotic reading of a historical event: the (alleged) demonic possession of a group of nuns in the convent of Loudun, in France, between 1632 and 1638. Possession emblematizes one of the most radical forms, in our culture, of confrontation with the Other, and of the battle undertaken (by exorcists, doctors, politicians) to get over it. The battle against possession can be defined as a properly “semiotic” battle since it is based on a work of interpretation of the “language” of the Other, of the semiotic systems through which it expresses itself and through which it reveals itself, and on a work of symbolic production aimed at developing formulas, words, images capable of “hurting” him and making him retreat.he battlefield of this symbolic struggle, in Loudun, is the body of the possessed, which from the imposition of an absence (as religious and as women) becomes the focal center of social attention and of female awareness itself: ostentatious, observed, beaten, desired, is the body that the conflicting factions try to appropriate. The “case” is studied starting from the treatment of the events that has been proposed by historians (Michelet), scholars of mysticism (De Certeau), novelists (Dumas, Huxley, in particular), film directors (Russell, Kawalerowicz), each of whom offers particular perspectives on this battle.